Reflections on the Use of a Smartphone to Facilitate Qualitative Research in South Africa - Matlala, Sogo France; Matlala, Makoko Neo (Qualitative Report, 2018)
This paper describes conditions that led to the use of a smartphone to collect qualitative data instead of using a digital voice recorder as the standard device for recording of interviews. Through reviewing technical documents, the paper defines a smartphone and describes its applications that are useful in the research process. It further points out possible uses of other applications of a smartphone in the research process. The paper concludes that a smartphone is a valuable device to researcher
Article published in the Qualitative Report
Keywords: Document Review; Qualitative Research; Smartphone; Smartphones; Research--Data processing; Research--Equipment and supplies